Die gebruik van die RRDI deur minder ervare sangonderwysers vir die kies van Suid-Afrikaanse lied repertorium vir sangeresse - Van Lill, Adre (Stellenbosch : Stellenbosch University, 2017)
ENGLISH ABSTRACT: Singing teachers need fundamental knowledge to be able to make good repertoire choices. There is, however, no standard model or procedure, according to which these choices can be made. Less skilled singing teachers can, owing to a lack of experience, struggle with this process. Singing teachers who have been doing this for a number of years, have various types of knowledge, or what David Elliott refers to as educatorship. This enables them to use the best practice for selecting repertoire. This study examines a rating model, the Ralston Repertoire Difficulty Index (RRDI) that could possibly assist less experienced singing teachers in selecting repertoire. Questionnaires were completed by less experienced teachers in order to gain insight into the methods they employ. This verified whether there is a need for a rating model. The RRDI can unfortunately not be accepted on face value alone, because the model does not focus on a South African perspective. The advantages and challenges of the RRDI must therefore be examined in our context. The Grade 4 to 7 singing syllabus of the most acknowledged external music examination body in South Africa, the University of South Africa (UNISA), was used as case study. Eight songs by South African composers were analysed in two different ways. The first analysis focused on information obtained from interviews with more experienced singing teachers. The data from the interviews was analysed by means of content analysis. The second analysis utilized the original RRDI to determine the degree of difficulty of each song. A comparison of these two analyses indicates the usefulness and limitations of the model. It was found that the seven criteria of the RRDI can serve as a good departure for determining the degree of difficulty of a song. By making adjustments to the model, this can be a valuable tool that can give less experienced singing teachers a head start in developing their educatorship.